When do host country nationals help expatriates? The roles of identification with the multinational enterprise and career development support by the subsidiary - YAMAO, Sachiko (Institutional Knowledge at Singapore Management University, 2020)
One of the concerns of host country nationals (HCNs) who work alongside expatriates in subsidiaries of multinational enterprises (MNEs) is their career prospects in the organization. This study advances the literature of expatriate management in MNEs by spotlighting the roles of the HCNs’ identification with the MNE and career development support received by the HCNs as key factors affecting the HCNs’ decisions to provide help to expatriates. According to the data collected in four countries (Australia, China, India, and Singapore), the HCNs’ identification with the MNE and their perceived subsidiary support for career development are positively related to their extra-role helping behavior toward the expatriates. Further, the positive relationship between MNE identification and extra-role helping behavior becomes stronger when the subsidiary’s career development support is high. We also provide post-hoc analyses to explore the potential differences of the four host countries in these relations.